The role of the national drug law enforcement agency in the curtailment of youth involvement in drug abuse in Ilorin, Kwara State, Nigeria - Moshood, Issah (Acta criminologica, 2018)
In recent times, the trend of drug and substance abuse among youths in Ilorin, Nigeria, has been so alarming that it has generated serious concerns from all quarters in the city. In spite of the efforts of the Nigerian National Drug Law Enforcement Agency (NDLEA) (Ilorin Command), the menace continues to eat deep into the social and cultural fabrics of the metropolis. Therefore, the aim of this study is to examine the perceived causes of the proliferation of drug abuse, as well as to suggest tactics and programs that should be employed in curtailing the proliferation of drug abuse in Ilorin (Nigeria). The Social Disorganisation Theory and the Contingency Theory were used to frame this study. This study was purely quantitative. Purposively, four drug-prone areas in Ilorin, Nigeria (Idi-Ape, Oja-Oba, Ile-Film and Gambari) were selected. From these areas, a total sample size of 1 400 was purposively selected (350 respondents purposively selected from each of the selected areas). Questionnaires were used as an instrument for data collection, because of the relatively large number of the respondents. The study found that high concentration of unemployed youths, presence of dilapidated and uncompleted buildings and the presence of law-violating gangs dealing in narcotic drugs in the neighbourhoods were the perceived causes of the proliferation of drug abuse in Ilorin (Nigeria). The study also found that regular patrols of drug-prone areas in Ilorin, as well as putting in place measures to eradicate the cultivation of narcotic drugs, would help in eliminating drug abuse in Ilorin, Nigeria. Based on these findings, the study suggests that any tactics and programs for curbing the proliferation of drug abuse should be contingent on the specific circumstantial factors inherent in the drug-prone areas in Ilorin (Nigeria).